Psychological Empowerment and Psychological Well-Being as Job Performance Mediators - Putra, Alfa Santoso Budiwidjojo; Kusumawati, Evi Dewi; Kartikasari, Dewi (Journal of Business Management and Economic Development, 2024)
This study aims to investigate the relationship between perceived organizational support (POS), psychological empowerment, psychological well-being, and job performance among 150 employees in the Indonesian telecommunications sector. This sample size aligns with the requirements for Structural Equation Modeling (SEM) analysis. Data was collected through a questionnaire using a Likert scale with two parts, covering respondent profiles and research variables. SmartPLS was employed for data analysis, and various tests were conducted to ensure data reliability, convergent validity, and discriminant validity. The findings highlight key factors influencing job performance in this context. Firstly, psychological empowerment has a significant positive impact on job performance, emphasizing the importance of empowering employees for enhanced productivity. Secondly, psychological well-being also significantly influences job performance, indicating the connection between employees' mental health and their job performance. Interestingly, perceived organizational support (POS) itself doesn't directly impact job performance but indirectly influences it through the mediation of psychological empowerment. In other words, strong organizational support boosts employees' empowerment, leading to improved job performance. The study also underscores the joint mediating roles of psychological empowerment and psychological well-being, suggesting that organizations should focus on enhancing POS while nurturing empowerment and well-being to optimize job performance.